Development of a Modular Operando Cell for X-ray Imaging of Strongly Absorbing Silver-Based Gas Diffusion Electrodes. Issue 4 (1st April 2022) - Hoffmann, Hendrik; Paulisch, Melanie Cornelia; Gebhard, Marcus; Osiewacz, Jens; Kutter, Maximilian; Hilger, André; Arlt, Tobias; Kardjilov, Nikolay; Ellendorff, Barbara; Beckmann, Felix; Markötter, Henning; Luik, Marius; et al.
Abstract : Metal-based gas diffusion electrodes are utilized in chlor-alkali electrolysis or electrochemical reduction of carbon dioxide, allowing the reaction to proceed at high current densities. In contrast to planar electrodes and predominantly 2D designs, the industrially required high current densities can be achieved by intense contact between the gas and liquid phase with the catalytically active surfaces. An essential asset for the knowledge-based design of tailored electrodes is therefore in-depth information on electrolyte distribution and intrusion into the electrode's porous structure. Lab-based and synchrotron radiography allow for monitoring this process operando . Herein, we describe the development of a cell design that can be modularly adapted and successfully used to monitor both the oxygen reduction reaction and the electrochemical reduction of CO2 as exemplary and currently very relevant examples of gas-liquid reactions by only minor modifications to the cell set-up. With the reported cell design, we were able to observe the electrolyte distribution within the gas diffusion electrode during cell operation in realistic conditions.